Exposure to cooking oil fumes and chronic bronchitis in nonsmoking women aged 40 years and over: a health-care based study - Huang-Chi Chen; Chia-Fang Wu; Inn-Wen Chong; Ming-Tsang Wu (BMC, 2018)
Abstract Background Little is known about the effect of exposure to cooking oil fumes (COFs) on the development of non-malignant respiratory diseases in nonsmoking women. This study investigated the relationship between exposure to COFs and chronic bronchitis in female Taiwanese non-smokers. Methods Searching the 1999 claims and registration records maintained by Taiwan's National Health Insurance Program, we identified 1846 women aged 40 years or older diagnosed as having chronic bronchitis (ICD-9 code: 491) at least twice in 1999 as potential study cases and 4624 women who had no diagnosis of chronic bronchitis the same year as potential study controls. We visited randomly selected women from each group in their homes, interviewed to collect related data including cooking habits and kitchen characteristics, and them a spirometry to collect FEV1 and FVC data between 2000 and 2009. Results After the exclusion of thirty smokers, the women were classified those with chronic bronchitis (n = 53), probable chronic bronchitis (n = 285), and no pulmonary disease (n = 306) based on physician diagnosis and American Thoracic Society criteria. Women who had cooked ≥ 21 times per week between the ages of 20 and 40 years old had a 4.73-fold higher risk of chronic bronchitis than those cooking < 14 times per week (95% CI = 1.65-13.53). Perceived kitchen smokiness was significantly associated with decreased FEV1 (− 137 ml, p = 0.021) and FEV1/FVC ratio (− 7.67%, p = 0.008). Conclusions Exposure to COF may exacerbate the progression of chronic bronchitis in nonsmoking women.